Role of Substrate in Au Nanoparticle Decoration by Electroless Deposition - Luca Bruno; Mario Urso; Yosi Shacham-Diamand; Francesco Priolo; Salvo Mirabella (Nanomaterials, 2020)
Decoration of nanostructures is a promising way of improving performances of nanomaterials. In particular, decoration with Au nanoparticles is considerably efficient in sensing and catalysis applications. Here, the mechanism of decoration with Au nanoparticles by means of low-cost electroless deposition (ELD) is investigated on different substrates, demonstrating largely different outcomes. ELD solution with Au potassium cyanide and sodium hypophosphite, at constant temperature (80 °C) and pH (7.5), is used to decorate by immersion metal (Ni) or semiconductor (Si, NiO) substrates, as well as NiO nanowalls. All substrates were pre-treated with a hydrazine hydrate bath. Scanning electron microscopy and Rutherford backscattering spectrometry were used to quantitatively analyze the amount, shape and size of deposited Au. Au nanoparticle decoration by ELD is greatly affected by the substrates, leading to a fast film deposition onto metallic substrate, or to a slow cluster (50–200 nm sized) formation on semiconducting substrate. Size and density of resulting Au clusters strongly depend on substrate material and morphology. Au ELD is shown to proceed through a galvanic displacement on Ni substrate, and it can be modeled with a local cell mechanism widely affected by the substrate conductivity at surface. These data are presented and discussed, allowing for cheap and reproducible Au nanoparticle decoration on several substrates.